The effect of parasitic charge on the output stability of MEMS gyroscopes *Project supported by the National Natural Science Foundation of China (No. 61504130). (August 2018) - Liu, Nan; Su, Yan; Tong, Xin; Han, Guowei; Si, Chaowei; Li, Zhaofeng; Ning, Jin
Abstract: Output voltage drifting was observed in MEMS gyroscopes. Other than the quadrature error, frequency mismatch and quality factor, the dielectric parasitic charge was thought to be a major determinant. We studied the mechanism and variation of the parasitic charge in the MEMS gyroscopes, and analyzed the effect of the parasitic charge on the output stability. This phenomenon was extremely obvious in the Pyrex encapsulated MEMS gyroscopes. Due to the DC voltage required for the electrostatic actuation, the parasitic charge in the dielectric layer would accumulate and induce a residual voltage. This voltage had an impact on the resonant frequency of the gyroscopes, so as to affect the output stability. The theoretical studies were also confirmed by our experimental results. It was shown that the parasitic charge was harmful to the output stability of MEMS gyroscopes.